p27(Kip1) and p21(Cip1) Are Not Required for the Formation of Active D Cyclin-cdk4 Complexes - Bagui, Tapan K. (American Society for Microbiology, 2003)
Our studies address questions pertaining to the regulation of D cyclin-cdk4 activity, and the following results were obtained. Conditions that increased the abundance of the D cyclins also increased the abundance of enzymatically active D cyclin-cdk4 complexes in mouse embryo fibroblasts (MEFs) lacking both p27(Kip1) and p21(Cip1) (p27/p21(−/−)). Such conditions included ectopic expression of cyclin D1 and inhibition of D cyclin degradation by the proteasome inhibitor MG132. However, as determined by treatment of wild-type MEFs with MG132, maximal accumulation of D cyclin-cdk4 complexes required p27(Kip1) and p21(Cip1) and coincided with the formation of inactive D cyclin-cdk4-p27(Kip1) or -p21(Cip1) complexes. p27(Kip1) or p21(Cip1) also increased the abundance of D cyclin-cdk4 complexes and reduced amounts of cdk4 activity when ectopically expressed in p27/p21(−/−) MEFs. Lastly, increases in the stability of the D cyclins accounted for their greater abundance in wild-type MEFs than in p27/p21(−/−) MEFs. We conclude that (i) D cyclin-cdk4 complexes are formed and become active in the absence of p27(Kip1) and p21(Cip1) and (ii) p27(Kip1) and p21(Cip1) maximize the accumulation but inhibit the activity of D cyclin-cdk4 complexes. We suggest that D cyclin-cdk4 complexes are more stable when bound to p27(Kip1) or p21(Cip1) and that formation of ternary complexes also stabilizes the D cyclins.